LMI Based Fuzzy Control of a Wing Doubled Fractional-Order Chaos - Bin Wang; Yuzhu Wang; Hongbo Cao; Delan Zhu (Journal of Control Science and Engineering)
This paper investigates a new wing doubled fractional-order chaos and its control. Firstly, a new fractional-order chaos is proposed, replacing linear term x in the second equation by its absolute value; a new improved system is got, which can make the wing of the original system doubled. Then, circuit diagram is presented for the proposed fractional-order chaos. Furthermore, based on fractional-order stability theory and T-S fuzzy model, a more practical stability condition for fuzzy control of the proposed fractional-order chaos is given as s set of linear matrix inequality (LMI) and the strict mathematical norms of LMI are presented. Finally, numerical simulations are given to verify the effectiveness of the proposed theoretical results.